Devirsifikasi Perusahaan dan Manajemen Laba pada Perusahaan Manufaktur - Azlina, Azlina; Agustina, Agustina (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study sought to ascertain the impact of diversification firms on income smoothing in manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. The study's data analysis approach uses multiple linear regression to predict the effect of the independent variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. The sampling method in this study was purposive. The survey results show that diversification firm affects earnings management. Proves that when diversifying firms, it will become a multi-business company that is not only engaged in one line of business, the more diverse the industries the company has, the more sources of income the company will have.